How is the discourse of performance-based financing shaped at the global level?: a poststructural analysis - Gautier, Lara; De Allegri, Manuela; Ridde, Valéry (Globalization and health, 2019)
Performance-based financing (PBF) in low- and middle-income settings has diffused at an unusually rapid pace. While many studies have looked at PBF implementation processes and effects, there is an empirical research gap investigating the ways PBF has diffused. Discursive processes are paramount elements of policy diffusion because they explain the origins of essential elements of the political debate on PBF. Using Bacchi’s poststructural approach that emphasises problem representations embedded in the discourse, the present study analyses the construction of the global discourse on PBF.
Gesehen am 28.03.2019